Scientism, Anti-Science, and Scientific Activities as an Expression of Religious Beliefs - Jadi Sampurna Lima (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
This paper seeks to show how believers can carry out scientific activities or appreciate the results of scientific research as an expression of faith itself. This goal will be achieved by demonstrating two important distinctions, namely: 1) the difference between the rejecting scientism and anti-science stance, 2) the difference between rejecting scientism and accepting the reality of theism. Later, I will show how the narrative of conflict between the adherents of scientism and its opponents can be overcome by localizing the narrative of the conflict to local historical situations and at the end an alternative narrative taken from internal sources of the Christian religious tradition will be explained in relation to three things, namely: 1) assumptions about the relationship between faith and reason, 2) attitudes towards human critical efforts, and 3) attitudes towards nature and natural research activities. This proposal is expected to be an example of how science and faith can enrich each other in a dialogical-critical relationship.